The International Conference on Innovation, Management and Technology Research (ICIMTR 2012) - Universiti Malaysia Kelantan, Pusat Penyelidikan & Inovasi Keusahwanan (GERIC) (2012)
The International Conference on Innovation, Management and Technology Research (ICIMTR 2012) was officially launched on 21 May 2012; by YB Datuk Wira Latiff bin Datuk Tamby Chik who represented the Chief Minister of Malacca, Datuk Seri Hj Mohd Ali bin Mohd Rustam. ICIMTR 2012 is an ISI/SCOPUS indexed conference that is jointly organized by Universiti Malaysia Kelantan & Universiti Teknologi MARA. Also presence at the opening ceremony were the Vice Chancellor of Universiti Malaysia Kelantan (UMK); Professor Dr Faridah Hassan, Dean of the Faculty of Business & Management, Universiti Teknologi MARA (UiTM); Professor Trevor Bond & Professor Klaus Georg Oestreicher (both are key note speakers); Professor Dr Normah Omar of the Accounting Research Institute (ARI) and Professor Dr Raja Suzana, the conference chair. ICIMTR 2012 has originally received more than 280 papers but only 141 of them "passed" the blind review process. A total of 50 international participants from more than 25 countries are attending the two-day conference.